A concrete homogenisation technique at meso-scale level accounting for damaging behaviour of cement paste and aggregates. (September 2016) - Contrafatto, Loredana; Cuomo, Massimo; Gazzo, Salvatore
Highlights: Mesoscale non linear model of concrete with random generation of phases distribution. Method is efficient afor computational cost with respect to previous proposals. Non linear and damage behaviour of concrete obtained from properties of the constituents. Experiments on the constituents and on concrete samples have been performed. The behaviour of concrete has been reproduced up and beyond the peak stress. Abstract: Concrete is an heterogeneous structural material whose constitutive behaviour is strictly depending on the mechanical properties of the aggregates and the cement paste. A large number of methods have been devoted to the prediction of the mechanical properties of this material by means of meso-scale analysis. The paper concerns a new meso-scale model of concrete, that considers the composite as a multi-phase material. The numerical description of the meso-scale structure is attained using a random method that allocates at each Gauss point of the finite element discretisation of the Representative Volume Element (RVE) a specific phase of the mixture: aggregate, cement paste, void. Each phase is characterised by a specific non linear constitutive model, whose parameters have been determined by means of experimental tests on the components. More experimental tests have been performed on concrete samples, and they have been numerically reproduced by means of the proposed procedure. Numerical simulations of cyclic uniaxial compression tests have shown the ability of the meso-model to correctly predict the peak strength, the tangent and secant elastic stiffness of the mixture for strains above the peak strain, even adopting a relatively coarse finite element discretisation of the RVE.